Transmission and Transformation of Cacak Burung Symbolism in Banjar Community - Nadhiraturrahmi Aidina; Rijal Ali; Nada Rahmatina; Siti Hafsah (Center for Research and Development of Religious Literature and Heritage, 2024)
Although the majority of the Banjar tribe today embraces Islam, elements of pre-Islamic culture have acculturated and remain relevant in their daily lives. One such element is the cacak burung symbol. Rooted in the traditional beliefs of the pre-Islamic Dayak tribe, the cacak burung symbol has persisted into the present-day Banjar society, now with an Islamic identity. This persistence necessitates a process of transmission and transformation in its development. This study examines the diachronic transformation of the cacak burung symbol, aiming to reinterpret and ensure its continuity in various contexts. The study addresses three main questions: (1) What is the history and use of the cacak burung symbol in the pre-Islamic Dayak tradition? (2) How has the use of the cacak burung symbol evolved from the post-Islamization era to the present? (3) What is the process of transmission and transformation of the cacak burung symbol in Banjar society? This qualitative research employed descriptive analysis xmethod. Through observations of the cacak burung symbol in traditional Banjar practices and interviews, the study concludes that the symbol is transmitted from generation to generation through discursive traditions. This transmission pattern necessitates transformations in the reading mantra, material, and form of the symbol. These transformations are influenced by the Islamization of the Dayak-Banjar tribe, adaptations to a busier lifestyle, and the impact of globalization.